Hubungan Penggunaan Gadget terhadap Kelainan Refraksi di SD Semarang - Junaedi, Machbu; Kholil, Mochammad (SENTRI: Jurnal Riset Ilmiah, 2025)
Gadget use among school-aged children has become a common phenomenon, both to support academic activities and as a means of entertainment. However, excessive use has the potential to negatively impact eye health, particularly in the development of refractive errors such as myopia and astigmatism. The aim was to analyze the relationship between the duration of gadget use and the emergence of refractive errors in students. The research approach used was quantitative with a survey method. Data were analyzed using a Chi-Square test to identify the relationship between the duration of gadget use (<4 hours and >4 hours per day) and the type of refractive error in 30 respondents. The test results showed a p-value of 0.063, which exceeds the 0.05 significance limit. This indicates no significant relationship between the duration of gadget use and refractive errors in students. However, a trend was found to increase cases of refractive errors in students who used gadgets for more than four hours per day. Therefore, further research with a larger sample size and consideration of environmental variables and other visual habits is strongly recommended. Overall, the results of this study confirm that short-duration gadget use has not shown a significant effect on refractive errors in elementary school students.